Octadecyltrichlorosilane (OTS)-coated ionic liquid drops: Micro-reactors for homogenous catalytic reactions at designated interfaces - Zhang, Xiaoning; Cai, Yuguang (Beilstein Journal of Nanotechnology, 2012)
An ionic liquid (IL), 1-butyl-3-methylimidazolium chloride ([Bmim]Cl) can assemble on prefabricated carboxylic acid–terminated chemical patterns on octadecyltrichlorosilane (OTS) film. The chemical pattern controls the position, shape and size of the IL on the surface. After the IL assembly – by incubating IL drops assembled on sample surface in an OTS silane vapor – an OTS layer was coated on the IL drop surface which encapsulated the IL drop. The OTS-coated capsule can exist stably under aqueous solution. The OTS coating protected the IL drops from being instantaneously dissolved by other solutions. We found that a homogenous catalyst (FeCl3) dissolved in [Bmim]Cl can be assembled together on the chemical patterns and subsequently encapsulated together with [Bmim]Cl by OTS coating. The pinhole defects within the vapor-coated silane layer provide space for the catalyst inside the capsule and reactants outside the capsule to meet and react. When the OTS-coated capsule containing a FeCl3/IL mixture was soaked under H2O2 solution, the Fe3+ ions catalyzed the decomposition reaction of hydrogen peroxide at the vapor-coated OTS-water interface. Since the shape and position of the interface is defined by the underneath chemical pattern, our findings show that the OTS-coated IL drops assembled on chemical patterns can be used as novel micro-reactors. This allows homogenous catalytic reactions to occur at the designated interfaces.
Keywords: AFM; catalyst encapsulation; chemical pattern; ionic liquid; OTS